(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Most of the building material for construction of houses is the normal brick. The rapid growth in today’s construction industry has obliged the civil engineers in searching for more efficient and durable alternatives far beyond the limitations of the conventional brick production